(untitled) (Physical Education, Health and Social Sciences, 2024)
Soil cartography with next-generation Geographic Information Systems (GIS), Global Positioning Systems (GPS), and Remote Sensing (RS) can greatly contribute to social resilience by helping optimize soil fertility with precise mapping in Punjab, a fertile region of Pakistan. This article attempts to synthesize how these tools can effectively tackle soil degradation, food security, and social resilience against floods and salinity-induced environmental shocks. It attempts to draw on existing literature to outline policy implications and recommendations for incorporating these tools into Punjab’s agricultural policies.